Do patients with diabetes with new onset acute myocardial infarction present with different symptoms than non-diabetic patients? - Schmitz, Timo; Wein, Bastian; Raake, Philip; Heier, Margit; Peters, Annette; Linseisen, Jakob; Meisinger, Christa (Frontiers in Cardiovascular Medicine, 2024)
The objective of this study was to investigate the differences in presenting symptoms between patients with and without diabetes being diagnosed with an acute myocardial infarction (AMI).Methods: A total of 5,900 patients with a first-time AMI were included into the analysis. All patients aged between 25 to 84 years were recorded by the population-based Myocardial Infarction Registry in Augsburg, Germany, between 2010 and 2017. The presence (yes/no) of 11 AMI typical symptoms during the acute event was assessed within the scope of a face-toface interview. Multivariable adjusted logistic regression models were calculated to analyze the associations between presenting symptoms and diabetes mellitus in AMI patients.Results: Patients with diabetes had significantly less frequent typical pain symptoms, including typical chest pain. Also, other symptoms like sweating, vomiting/nausea, dizziness/vertigo and fear of death/feeling of annihilation occurred significantly more likely in non-diabetic patients.The only exception was the symptom of shortness of breath, which was found significantly